Bilateral closed flexor pollicis longus musculotendinous junction ruptures - Qureshi, Arham (BMJ Case Rep, 2015)
We present a case of bilateral closed flexor pollicis longus musculotendinous junction ruptures. Our case suggests multifactorial aetiology and provides further evidence for genetic influences in musculotendinous junction injuries.